A CASE REPORT OF A SUBMUCOSAL FIBROID COMPLICATED BY VAGINAL PROLAPSE AND IMPACTION IN A LOW-RESOURCE SETTING. - Bwire, Innocent; Bwaga , Ibrahim; Mwinda, Richard; Mitengezo , Jean Paul; Mkojera, Josiah (Student’s Journal of Health Research Africa, 2024)
Background The most common female pelvic tumors that originate from the smooth muscle of the myometrium are called leiomyoma. Although leiomyomas are benign when they are Submucosal, they have the potential to prolapse into the vagina. The traditional method of treating pedunculated fibroid is vaginal myomectomy, however, it cannot always be carried out securely. The purpose of this case report is to illustrate the surgical difficulties when dealing with a large prolapsed pedunculated submucous fibroid. Customized surgical methods allow safe and efficient access to the prolapsed pedunculated fibroid stalk during hysterectomy. Case presentation This case involves a 53-year-old perimenopausal female with abnormal uterine bleeding. She had a large prolapsed pedunculated submucous fibroid, with anemia and infection. A modified total abdominal hysterectomy was performed, along with a unilateral sapingo-ophorectomy. The lump was determined by the histopathology report to be a benign leiomyoma without any indication of malignancy. Conclusions Regardless of its benignant nature, a large pedunculated submucous leiomyoma presents surgical difficulties during abdominal hysterectomy especially when vaginal prolapse is present and vaginal removal cannot be safely and easily performed. Factors such as parity, fertility desire, hemodynamic stability, prolapsed fibroid size, mobility of fibroid in the vagina, visibility, and size of the stalk need to be evaluated when deciding on the choice of surgical procedures. Recommendations The management of a submucosal fibroid with vaginal prolapse should be evaluated carefully and surgical difficulties anticipated when a vaginal myomectomy cannot be done. A prolapsed fibroid size greater than 6cm with the invisibility of the fibroid stalk should warrant consideration of customized approaches, however, no single factor can independently predict the operation of choice and its outcomes.